National Geographic kids almanac 2026. - National Geographic Partners (U.S.) (Washington, D.C., 2025)
This "edition of [the] ... almanac features tons of updated and new content, including new species discoveries, cutting-edge nature and space information, all-new games and jokes, and more. Practical reference material, including fast facts and maps of every country, has been fully updated. Homework help on key topics is sprinkled throughout the book"--
Your world 2026 -- Greatest breakthroughs -- Amazing animals -- Space and Earth -- Awesome exploration -- Fun and games -- Laugh out loud -- Culture connection -- Science and technology -- Wonders of nature -- History happens -- Geography rocks.
Includes index.
Keywords: Curiosities and wonders; Almanacs; Juvenile literature; Almanacs, Children's.; Juvenile literature; Almanacs, American; Curiosities and wonders; Trivia and miscellanea; Almanacs